2022
DOI: 10.3390/ijerph19158917
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Effect of Virtual Water Transfer on Water Quantity Conflict in Transboundary Rivers—Taking Ili River as a Case

Abstract: Water stress in countries within a drainage basin exacerbates the water quantity conflict in transboundary rivers. However, few studies considered the invisible effect of virtual water transfer on water quantity conflict by intensifying water stress. Therefore, this study, with Ili River as the case, collects data on Virtual Water Trade (VWT) from 1990 to 2015, uses water stress index (WSI) to assess water stress values under two scenarios (with or without virtual water transfer), and takes Grey Verhulst Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Thus, VWT needs to be converted from the provincial level to the riparian level. However, a few studies that focus on this topic convert VWT using the water efficiency coefficient [50][51][52]. Therefore, this paper also employed the proportion of the riparian water efficiency coefficient to the provincial water efficiency coefficient to quantify and convert the provincial VWT.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, VWT needs to be converted from the provincial level to the riparian level. However, a few studies that focus on this topic convert VWT using the water efficiency coefficient [50][51][52]. Therefore, this paper also employed the proportion of the riparian water efficiency coefficient to the provincial water efficiency coefficient to quantify and convert the provincial VWT.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of methodology, this paper, drawing from previous studies, thus constructed an index system grounded in principles of status quo, equity, efficiency, sustainability, and macro regulation. Second, as for VWT methodology, many scholars found that the multiregional input-output approach can clarify the interdependence among sections of an entire supply chain in an economy [53][54][55][56][57][58][59][60]. It provides a clearer quantification of the amount of water deployed in trade and makes the virtual water calculation more intuitive and accurate [53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Second, as for VWT methodology, many scholars found that the multiregional input-output approach can clarify the interdependence among sections of an entire supply chain in an economy [53][54][55][56][57][58][59][60]. It provides a clearer quantification of the amount of water deployed in trade and makes the virtual water calculation more intuitive and accurate [53][54][55][56][57][58][59][60]. Therefore, this paper drew an input-output tablet for modelling to calibrate water resources allocation in trade [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%